A method for automated generation of exercises with similar level of complexity - Mendes, João; Marcos, João (Anais do Workshop Brasileiro de Lógica (WBL), 2023)
The effort put by an educator on the manual construction of questions may be reduced if one uses tools for the automated generation of questions. Among these tools, only very few are able to control the level of complexity of their output, which ends up representing a challenge for the dissemination of individualized assessments. In the present study, we propose a method for the automated generation of exercises which uses the structure of the solution for the conjecture given as input in order to guarantee the similarity in the level of complexity of these exercises.